The Impact of Using Augmented Reality Patterns (Fixed Pattern, Moving Pattern) on the Academic Achievement for Basic Stage Students in Islamic Education Subject - Moustafa, Noor Belal; Altawalbeh, Manal Ata (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the impact of using augmented reality patterns (fixed pattern, moving pattern) on the academic achievement for basic stage students in Islamic education subject. To achieve the objective of this study, a quasi-experimental approach was used. The study sample was chosen in an intentional way as it consisted of (50) male and female students from the second-grade students in Elia’a Arab Schools. The study was conducted in the second semester (2021/ 2022). The sample was divided into two groups: the first experimental group consisted of (25) male and female students who were taught using augmented reality technology (fixed pattern), and the second one consisted of (25) male and female students who were taught using augmented reality technology (moving pattern). The assessment tool was prepared, which is the achievement test (pre and post) to get the results of the study, and the validity and reliability of the tool were verified. The results of the study showed that there were statistically significant differences between the two groups for the benefit of the second experimental group in the post-test, which was studied using augmented reality (moving pattern).
Keywords: Augmented Reality Patterns; Academic Achievement; Islamic Education Subject